Solve the equation:(x+3)/-3=(x+3)(x-1)

Divide both sides by (x+3), multipy both sides by -3.

I Will be happy to critique your work.

will it be x=-2?

no.

1=-3(x-1)
1=-3x+3
-2=-3x
x= 2/3

check that.

1. 👍
2. 👎
3. 👁

## Similar Questions

Quinda begins to solve the equation Negative 4.5 x + 3 = 2 minus 8.5 x by adding 8.5x to each side of the equation. Which next step would result in the variable terms and constant terms being on different sides of the equals sign?

2. ### math

A=1/2h (b1 + b2) Solve for b1 A=1/2h (b1 + b2) Solve for b1 I assume this is A = (1/2)(h)(b1 + b2); i.e., the h is in the numerator and not the denominator Multiply both sides by 2. 2A = (2*1/2)h(b1 + b2). 2*1/2 on the right side

3. ### Math

Which of the following is not a strategy for solving simple exponential equations? Question 12 options: a) Express both sides as powers with a common base and then equate the exponents. b) Divide both sides by the common base and

4. ### simultaneous equations

Solve 2a + b = 3 4a - 5b = 20 My attempt Multiply the first equation by 5 So, 10a + 5b = 15 4a - 5b = 20 Add them together 14a = 35 Divide both sides by 14 a = 2.5 Substitute (I have done it with the second one) 10 - 5b = 20 Take

Solve the inequality. Explain all steps and identify the properties used. 3a-4 less than or equal to 5 My answer: First, you add 4 to both sides: 3a - 4 + 4

2. ### Algebra

The first step to solve for y in y/3= 6 + x is A) to subtract x from both sides of the equation. B) to subtract y/3 from both sides of the equation. C) to divide each term on both sides of the equation by 3. ******* D) to multiply

3. ### Algebra

Which of the following describes a correct method for solving the equation below? -7/2n + 5 = -16 1. add 5 to both sides, then divide both sides by 2/7 2. subtract 5 from both sides, then multiply both sides by -7/2 3. add -5 to

4. ### algebra1

How do i solve this problem? 2(x-3)-3(x+5)=3(x-2)-7 what are the steps to solving this equation? HELP!!! Multply out the parentheses and then combine terms First step: 2x - 6 -3x -15 = 3x -6 -7 -x -21 = 3x -13 Nox add x + 13 to

1. ### math

Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T 8a+2=6b In the first example, divide both sides of the equation by 2 In the second example, add n to both sides of the equation. Try these yourself. They

2. ### science

rearrange this equation 2 make x the subect. 6y = 9 - 3x so first i add 3x to both sides which makes it 3x - 6y = 9 then do i divide both sides by 9 or wat?? can sum1 help me out here If they mean by "Make x the subject" the same

3. ### math

hi, i need help with solving this equation for "y" 2x+3y=-2 2x+3y=-2 Get y on one side. Subtract 2x from both sides. 2x-2x+3y=-2-2x combine terms. 3y=-2-2x Divide both sides by 3. 3y/3 = (-2-2x)/3 y = ?? how do you get -2-2x to

4. ### pre-algebra

Rewrite the equation so the variable is alone. Solve to find the value of the variable. 42=-2h Divide both sides by 2. Then change the signs of both sides. That will provide the answer. Possibly in 1 step: Divide by -ve 2